PENGARUH SENAM HAMIL MENGGUNAKAN BIRTH BALL TERHADAP PERSEPSI NYERI PADA PRIMIGRAVIDA SELAMA PERSALINAN - E.S , Wenny Indah Purnama; Tarawang, Vita Murniati; Nurihsan, Juntika (JURNAL KESEHATAN ALMUSLIM, 2019)
Pregnancy and childbirth are continous process of human reproductive. During pregnancy there is imbalance hormone induce physical changes and also psychological. Pregnancy exercise is one way to maintain the health of pregnant women and to prepare physically and mentally to achieve the birth. Coping strategies can assist in the pain management process. Exercise pregnancy use birth ball may facilitate capacity to cope pain labor, and physiological and psychological benefits. This study aims to analyze the effect exercise pregnancy use birth ball to pain perceptions on primigravida during labor. The research method use Quasi Experiment with pretest-posttest control grup design, with the sample of 34 primigravida at Midwife Private Clinic on Public Health Center Perumnas with sampling technique of sampling samples divided into two groups by random permuted blocks, each group was 17 respondents. Pain perceptions assessment using Visual Analogue Scale (VAS). The statistical test using Mann-Whitney tests to analize the difference on pain perceptions between the two study groups and use chi square to analize effect exercise pregnancy use birth ball on pain perceptions. The research showed that there is difference pain perceptions between intervention and control group (p=0,001), and there is effect exercise use of birth ball decerease on pain perceptions (p=0,004). Conclusion: Implementation of exercise pregnancy use birth ball effective to reduce pain perceptions among women in labor.